New Trends of Research in Ontologies and Lexical Resources: Ideas, Projects, Systems - Oltramari, Alessandro; Vossen, Piek; Qin, Lu; Hovy, Eduard (Theory and Applications of Natural Language Processing, 2013)
Surveying new directions of research and development in the interdisciplinary framework where ontologies and lexical resources intersect, this book deals with the complex relation between lexicons (in different languages) and the underlying ontological model.